(untitled) (مجلة إحالات, 2026)
This research paper aims to present a study of one of the most important areas of popular literature through analysis, explanation, and inference, which includes studying the effectiveness of Algerian popular proverbs in demonstrating the status of women in society and their superiority, and presenting demonstrations of their superiority in various areas of social life by classifying these proverbs in the form of semantic fields that show their significance. Its implicit meanings are external understanding and internal meanings. It also aims to clarify and explain the actual meanings of women’s position in society, which are not incompatible with the values and teachings of society and religion, by presenting common and commonly used models.